2004
DOI: 10.1002/ppul.10427
|View full text |Cite
|
Sign up to set email alerts
|

Early radiographic and clinical features associated with bronchiectasis in children

Abstract: Bronchiectasis among children living in developing regions is associated with respiratory infections during early childhood, but specific risk factors that precede childhood bronchiectasis are not fully characterized. We hypothesized that severe respiratory syncytial viral (RSV) infection in infancy would increase the risk of bronchiectasis among Alaska Native children in rural Alaska. This was a follow-up cohort study of a 1993-1996 case-control study of RSV-hospitalized case patients and their controls. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…Hence, the age of diagnosis of the bronchial disease did not correlate either with age or with specific diagnosis of primary immunodeficiency. Nevertheless, the overall tendency among the children studied who had PIDs was to develop bronchiectasis later than in patient groups reported by other authors, who identified this airway pathology in children at a mean age between 3 years [19,20] and 7 years [13]. It may be presumed that establishing the diagnosis of primary immunodeficiency and early institution of specific treatment with intravenous immunoglobulins and/or antibiotic therapy contributed to a slowdown in the airway and lung injury in our children.…”
Section: Bronchiectasis In Children With Primary Immune Deficiency DIcontrasting
confidence: 38%
See 1 more Smart Citation
“…Hence, the age of diagnosis of the bronchial disease did not correlate either with age or with specific diagnosis of primary immunodeficiency. Nevertheless, the overall tendency among the children studied who had PIDs was to develop bronchiectasis later than in patient groups reported by other authors, who identified this airway pathology in children at a mean age between 3 years [19,20] and 7 years [13]. It may be presumed that establishing the diagnosis of primary immunodeficiency and early institution of specific treatment with intravenous immunoglobulins and/or antibiotic therapy contributed to a slowdown in the airway and lung injury in our children.…”
Section: Bronchiectasis In Children With Primary Immune Deficiency DIcontrasting
confidence: 38%
“…Likewise, Redding and co-workers who evaluated a group of 10 children with bronchiectasis, demonstrated that the lung and hence airway injury which was manifested in chest radiographs predominantly as parenchymal densities or pneumonia rather than hyperinflation or atelectasis [19]. The radiological extent of bronchiectasis was the greatest in the left lower lobe (n = 5, 62.5%), followed by the right lower lobe (n = 4, 50%) and this localization mostly correlated with the diagnosis of profound antibody production defects, CVID and XLA; equally involved (in 2 cases, 25%, respectively) subsequently were the right middle lobe, the right upper lobe and the left upper lobe.…”
Section: Bronchiectasis In Children With Primary Immune Deficiency DImentioning
confidence: 99%
“…17,18 Because infant pneumonias in region A have been identified as a precursor to chronic respiratory diseases such as bronchiectasis and chronic productive cough, many of these children will likely have ongoing health problems because of these infections. 22,23 Because respiratory and skin infections are not typically contracted through water, the higher rates in low-water-service villages may appear paradoxical. This is best explained by the important role water plays in preventing respiratory and skin infections through handwashing and other personal hygienic measures.…”
Section: Discussionmentioning
confidence: 97%
“…An evaluation of 208 children from YK showed that 58% experienced x-ray-confirmed pneumonia before 2 years of age. 16 Pneumonia has been associated with later development of bronchiectasis in YK infants and indigenous children from Australia. 16 -18 Although palivizumab prophylaxis may explain the decrease in RSV hospitalizations in premature infants, it does not account for the RSV decline in term children.…”
Section: Discussionmentioning
confidence: 99%